When belief becomes research: conspiracist communities on the social web - Greer, Katie; Beene, Stephanie (Frontiers in Communication, 2024)
This article explores two QAnon subgroups that were not active during the initial phase of the movement but now epitomize how QAnon has capitalized on social media to reach more people. We examine these smaller communities through the lens of information literacy and other literacies to identify opportunities for librarians and educators. These groups illustrate the convergence of various conspiracy theories into the superconspiracy QAnon on two different social media platforms (Facebook and Telegram), as well as the dual notions of parasociality and cognitive authority to proliferate the QAnon worldview. The communities of conspiracy theorists explored here exhibit information behaviors distinct from the initial QAnon community, presenting opportunities for information professionals to employ new models of information literacy, metaliteracy, and other literacies to combat conspiracy ideation. Notable themes evidenced in both samples include an increasing religiosity affiliated with QAnon, affective states that promote conspiracy ideation, faulty hermeneutics and epistemologies, and specific literacy gaps. We must update our understanding of QAnon and its adherents' shifting priorities and behaviors. Through investigating these smaller subgroups, researchers and educators can address the evolution of the QAnon movement by teaching to literacy gaps and logical fallacies, and acknowledging the troubling emotions that undergird broader belief systems.